DIGITAL FINANCIAL LITERACY AND FINANCIAL WELL-BEING IN DIGITAL INVESTMENT: A SYSTEMATIC LITERATURE REVIEW (Proceeding of SINERGY, 2026)
The rapid growth of digital investment platforms has increased the importance of digital financial literacy and financial well-being in shaping individual financial behaviour. However, empirical findings on the relationship between these two constructs remain fragmented and context-dependent. This study aims to systematically review the existing literature on digital financial literacy and financial well-being in digital investment contexts.Using a systematic literature review approach, relevant peer-reviewed journal articles were identified through major academic databases, including Scopus, Web of Science, and Google Scholar. The selected studies were analyzed thematically to examine research trends, conceptualizations, measurement approaches, and key empirical findings.The review indicates that digital financial literacy is generally associated with higher levels of perceived financial security and control, which are core components of financial well-being. Nevertheless, variations in definitions, measurement instruments, and research contexts contribute to inconsistent results across studies. The findings also suggest that financial well-being may function as a psychological mechanism linking digital financial literacy to investment-related behaviour, although this role remains underexplored.This study contributes by synthesizing current evidence and identifying key research gaps, providing directions for future research on digital investment behaviour.